2020
DOI: 10.1161/strokeaha.119.026907
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy and Thrombolysis of Isolated Posterior Cerebral Artery Occlusion

Abstract: Background and Purpose— We investigated efficacy and safety of acute revascularization with intravenous thrombolysis (IVT) and endovascular treatment (EVT) in ischemic stroke from isolated posterior cerebral artery occlusion, by assessing recanalization, disability, visual, cognitive outcomes, and hemorrhagic complications. Methods— For this retrospective single-center cohort study, we selected all consecutive patients with stroke with isolated posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 30 publications
7
88
2
Order By: Relevance
“…There is only one other study so far comparing clinical outcome between these groups in patients with acute occlusions of the proximal PCA, i.e., in the P1 and P2 segment. The patient cohort in this retrospective study by Strambo et al ( 14 ) is similar to the present one in terms of patient numbers and demographic parameters. The initial symptom severity was equivalent, and there was a similar proportion of patients with premorbid disability, i.e., a mRS >2.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…There is only one other study so far comparing clinical outcome between these groups in patients with acute occlusions of the proximal PCA, i.e., in the P1 and P2 segment. The patient cohort in this retrospective study by Strambo et al ( 14 ) is similar to the present one in terms of patient numbers and demographic parameters. The initial symptom severity was equivalent, and there was a similar proportion of patients with premorbid disability, i.e., a mRS >2.…”
Section: Discussionsupporting
confidence: 63%
“…Imaging was primarily performed with computed tomography (CT) in 118 (91%) and CT angiography in 106 (81.5%) of the patients, while 32 (24.6%) had an MRI (21 patients had both consecutively, i.e., CT and MRI). Perfusion imaging with either MRI or CT was performed in 31 (23.8%) of the patients, and 23 (74%) of them had a visual mismatch, either on MRI ( 6 ) or on CT ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, 4 studies met the inclusion criteria and were included in this review (Table 1). [18][19][20][21] Details of the study flow are illustrated in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Only 3 studies reported a mortality rate at 90 days. [18][19][20] No difference in mortality at long-term follow-up was demonstrated in the meta-analysis of pooled data (Fig. 4), with low heterogeneity (OR 1.73, 95% CI 0.66-4.55; p = 0.263; I 2 = 0%).…”
Section: Clinical Outcomesmentioning
confidence: 92%